2022
DOI: 10.1371/journal.pone.0267117
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of GSEC/miR-101-3p/SNX16/PAPOLG axis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal malignancies. A growing number of studies have shown that competitive endogenous RNA (ceRNA) regulatory networks might play important roles during HCC process. The present study aimed to identify a regulatory axis of the ceRNA network associated with the development of HCC. The roles of SNX16 and PAPOLG in HCC were comprehensively analyzed using bioinformatics tools. Subsequently, the “mRNA-miRNA-lncRNA” model was then used to predict the upstream miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In the case of LUAD, GSEC played an active role in the promotion of tumor progression through the GSEC/miRNA-101-3p/CISD1 Axis and showed a significant association with ferroptosis, as confirmed by previous research 37 . Additionally, several research reported GSEC could promote the malignant process of triple-negative breast cancer and hepatocellular carcinoma via the GSEC/miR-202-5p/AXL axis and the GSEC/miR-101-3p/SNX16/PAPOLG axis 38 , 39 , respectively. Furthermore, lncRNA AL606834.1 has been used for prognostic models of lung adenocarcinoma and pancreatic cancer 40 , 41 , AL365181.2 has been applied in multiple prognostic models of lung adenocarcinoma 42 , 43 , and AC012615.1 has been studied in a prognostic model of glioblastoma 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of LUAD, GSEC played an active role in the promotion of tumor progression through the GSEC/miRNA-101-3p/CISD1 Axis and showed a significant association with ferroptosis, as confirmed by previous research 37 . Additionally, several research reported GSEC could promote the malignant process of triple-negative breast cancer and hepatocellular carcinoma via the GSEC/miR-202-5p/AXL axis and the GSEC/miR-101-3p/SNX16/PAPOLG axis 38 , 39 , respectively. Furthermore, lncRNA AL606834.1 has been used for prognostic models of lung adenocarcinoma and pancreatic cancer 40 , 41 , AL365181.2 has been applied in multiple prognostic models of lung adenocarcinoma 42 , 43 , and AC012615.1 has been studied in a prognostic model of glioblastoma 44 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA DLEU2 aggravates the progression of HCC ( Guo et al, 2019 ). Furthermore, the GSEC/miR-101-3p/SNX16/PAPOLG axis of the ceRNA network axis is an important factor associated with HCC prognosis and immune infiltration ( Hu et al, 2022 ). Our study revealed that these mRNA-miRNA-lncRNA networks were associated with the prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Shangshang Hu et al. constructed a GSEC/Mir-101-3p/SNX16/PAPOLG network to predict the prognosis of hepatocellular carcinoma ( 43 ). Xiulin Jiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Shangshang Hu et al constructed a GSEC/Mir-101-3p/SNX16/ PAPOLG network to predict the prognosis of hepatocellular carcinoma (43). Xiulin Jiang et al also found that ferroptosis-related GSEC-lncRNAs, mirNA-101-3p, and CISD1 axis play a functional role in lung adenocarcinoma (LUAD) and may serve as useful diagnostic and therapeutic biomarkers for the disease.…”
Section: Discussionmentioning
confidence: 99%